A case study of design decision-making for an exemplar steel portal-framed building under fire exposure using a hybrid analysis technique. (March 2020) - Akaa, Obinna Ukeni; Abu, Anthony; Spearpoint, Michael
Abstract: This paper demonstrates how stakeholder decision-making can be optimised in the design of steel-framed buildings that may be exposed to destructive fires. A novel hybrid technique, proposed in a previous study by the same authors, for combining stakeholder opinions on different fire protection options and probabilistic structural fire analysis outcomes is tested on an exemplar building. The hybrid analysis method is presented, followed by the description of the case study portal-framed building and the stakeholder engagement employed in the process. The remainder of the paper presents the qualitative and quantitative analyses outcomes and their integration to access an optimal design decision based on a decision management framework adapted from the risk management guidelines of AS/NZS ISO 31000:2009. The results show the seamless aggregation, prioritisation and synthesis of conflicting design decision attributes in ranking competing fire protection options to confirm the viability of the technique. The results also show that not protecting the steel members is the optimal/cost-effective option given the influence of participant-stakeholder weights and the building type. Highlights: Application of a hybrid decision analysis technique in the structural fire design of an exemplar steel building is demonstrated. Stakeholder influence as individuals and as a group, and uncertainties in a design decision-making process are addressed. Unprotecting the steel structural members is the optimal/cost-effective option for the exemplar building.